Prevention of Electrostatic Charge Generation in Filtration of Low-Conductivity Oils by Surface Modification of Modern Filter Media. Issue 3 (3rd May 2020) - Staudt, Johannes; Duchowski, John K.; Leyer, Stephan
Abstract: The electrostatic charging behavior of filter elements operating in various hydraulic and lubricating fluids has been re-examined from the perspective of fundamental material properties of the two materials participating in the event. In contrast to the previously proposed mechanisms that focused predominantly on fluid and material conductivities, new evidence strongly suggests that the relative placement of the substrates in the triboelectric series must be taken into account. The positions occupied in the triboelectric series account for the donor/acceptor tendencies exhibited by the materials when brought close together in close proximity (≤10 nm). Nevertheless, this behavior is only an outward manifestation of the deeper underlying characteristics that include material surface energies and, looking even deeper, the associated electron work functions of the interacting materials. Herein we provide several examples of the enhanced understanding of the electrostatic charging/discharging (ESC/ESD) phenomena as they occur in the course of filtration of hydraulic and lubricating fluids through modern filter elements constructed of synthetic glass fiber and polymer materials.